High-throughput manufacturing of epitaxial membranes from a single wafer by 2D materials-based layer transfer process - Kim H.; Liu Y.; Lu K.; Chang C.S.; Sung D.; Akl M.; Qiao K.; Kim K.S.; Park B.-I.; Zhu M.; Suh J.M.; Kim J.; et al. (Nature Research, 2024)
Layer transfer techniques have been extensively explored for semiconductor device fabrication as a path to reduce costs and to form heterogeneously integrated devices. These techniques entail isolating epitaxial layers from an expensive donor wafer to form freestanding membranes. However, current layer transfer processes are still low-throughput and too expensive to be commercially suitable. Here we report a high-throughput layer transfer technique that can produce multiple compound semiconductor membranes from a single wafer. We directly grow two-dimensional (2D) materials on IIIN and IIIV substrates using epitaxy tools, which enables a scheme comprised of multiple alternating layers of 2D materials and epilayers that can be formed by a single growth run. Each epilayer in the multistack structure is then harvested by layer-by-layer mechanical exfoliation, producing multiple freestanding membranes from a single wafer without involving time-consuming processes such as sacrificial layer etching or wafer polishing. Moreover, atomic-precision exfoliation at the 2D interface allows for the recycling of the wafers for subsequent membrane production, with the potential for greatly reducing the manufacturing cost. 2023, The Author(s), under exclusive licence to Springer Nature Limited.